A Case of Pulmonary-Renal Syndrome Leading to the Diagnosis of Legionnaires' Disease. (23rd November 2016) - Sabani, Erasmia; Sarafidis, Pantelis A.; Lazaridis, Antonios; Kouloukourgiotou, Theodora; Stylianou, Konstantinos; Pantzaki, Afroditi; Papagianni, Aikaterini; Efstratiadis, Georgios
Abstract : We report a case of a 51-year-old Caucasian man referred at our department due to acute renal failure (ARF) complicating respiratory failure during hospitalization in a regional hospital. The patient was previously started on steroids due to the suspicion of rapidly progressive glomerulonephritis (RPGN) in the context of Goodpasture syndrome. However, clinical and laboratory findings did not support this diagnosis; instead a careful evaluation limited differential diagnosis of the renal insult to acute tubular necrosis or acute interstitial nephritis (AIN) following respiratory infection. With lung function fully improved but renal function not recovering, a renal biopsy revealed AIN, a finding leading to further diagnostic testing and finally to the diagnosis of Legionnaires' disease as a cause of this patient's pulmonary-renal syndrome. The management consisted of progressive tapering of oral steroids associated with full recovery of the patient's renal function. This is a rare case of Legionnaires' disease causing immune-mediated AIN and highlights the possibility of Legionella infection as a cause of pulmonary-renal syndrome.